Diversity and functional annotation of bacteria community associated with the epithelial surface of Hippocampus kuda (yellow seahorse) and its surrounding environment - NOEL JOHN IAN FEBEN S. MAGUATE; SHARON ROSE M. TABUGO (Society for Indonesian Biodiversity, 2024)
Abstract. Maguate NJIFS, Tabugo SRM. 2024. Diversity and functional annotation of bacteria community associated with the epithelial surface of Hippocampus kuda (yellow seahorse) and its surrounding environment. Biodiversitas 25: 2230-2240. Hippocampus kuda, commonly known as the yellow seahorse, hosts various microorganisms crucial for its well-being and interactions within its ecosystem. This research aimed to analyze and understand the bacterial community associated with H. kuda by employing V3-V4 16S rRNA gene amplicon sequencing on the Illumina MiSeq platform. Four distinct libraries were constructed, representing the epithelial surfaces of both male and female seahorses and samples from water and soil/sediment habitats. Following rigorous quality control and processing, 187,972 Amplicon Sequence Variants (ASVs) were identified. The predominant ASVs were attributed to genera such as Vibrio, Roseobacter, Photobacterium, Ruegeria, Candidatus, Pseudoalteromonas, Synechococcus, Flavobacterium, and Altererythrobacter, along with some unidentified genera belonging to the Proteobacteria phylum. As indicated by the Shannon index, alpha diversity analysis demonstrated the highest bacterial diversity on the epithelial surface of male seahorses (MS), with a value of 3.2363. Moreover, the functional annotation of bacterial community was conducted using the PICRUSt algorithm within the Parallel-Meta Suite (PMS) software. This analysis uncovered various functional categories, such as metabolism, genetic information processing, and cellular processing. Overall, the findings underscore the role of the microbiome on the skin and surrounding environment in influencing the growth and health of H. kuda seahorses. Notably, this study represents the first documentation of the bacterial community inhabiting the epithelial surface of H. kuda, shedding light on its significance in the ecology of these marine organisms.